Jojoba Oil-based Nano-emulsion as Promise Bio-pesticides against Myzus persicae and Tetranychus urticae and their Biosafety on Coccinella undecimpunctata and Aphid mummies - Doaa El sherif; Sherin Safar (Arab Universities Journal of Agricultural Sciences)
Nano-emulsion-based essential oils are considered the most effective applications for controlling pests. Jojoba oil-based nano-emulsion and bulk emulsion formulations were examined against Tetranychus urticae and Myzus persicae and their natural enemies. The prepared jojoba oil-based nano-emulsion showed superior stability in centrifuging and freezing tests and had non-foaming properties. The droplet size of the Jojoba oil-based nano-emulsion was as small as 45±5 nmwith a zeta potential of 4.79 mV. Results confirmed that jojoba oil-based nano-emulsion possesses better acaricidal and algicidal activity than bulk emulsion. The LC50 of nano-emulsion was 0.103 and 0.06%, while in bulk emulsion, it recorded 4.06 and 4.76% against T. urticae after 24 h of spraying at temperatures of 20 and 30oC, respectively. Under the same conditions, nano-emulsion had an LC50 value of 0.23 and 0.35% while bulk emulsion had 5.14 and 3.61% against M. persicae. Furthermore, the use of jojoba oil-based emulsion had no significant negative impact on aphid mummies or Coccinella undicempunctata. These encouraging findings confirmed that jojoba-based nano-emulsions possess potential eco-friendly and effective bio-pesticides against mites and aphids as well as being safe as biological control agents. Additionally, its physical properties are suitable for commercial use.